Pengaruh Tren, Gaya Hidup Berbelanja dan Harga Diskon terhadap Pembelian Impulsif Fashion Halal - Mila Safitri; Ida Farida; Rahma Hidayati Darwis (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to help understand how trends, shopping lifestyles and discount prices can influence impulse buying decisions of halal fashion users in the context of young Muslim consumers who are increasingly exposed to global trends and easy access to information, especially among FEBI IAIN Bone students who have not been widely discussed in previous studies. This research is a descriptive study using quantitative methods. Purposive Sampling is the sampling technique used, for the number of samples in this study took as many as 100 respondents who were used as research samples based on the results of the calculation of the slovin formula used. Structural Equation Modeling (SEM) is a component-based data analysis technique that utilizes Partial Least Squares (PLS) analysis tools. The results of this study prove that trends have a significant effect on impulse purchases of halal fashion as indicated by a T-Statistic of 2.987 > 1.96 and a p-value of 0.003 < 0.05. Shopping lifestyle has a significant effect on impulse purchases of halal fashion, as indicated by a T-Statistic of 2.242 > 1.96 and a p-value of 0.025, Discount prices have a significant effect on impulse purchases of halal fashion, as indicated by a T-Statistic of 1.972 > 1.96 and a p-value of 0.049 < 0.05